Efeito inibitório de micropartículas de vidro bioativo dopado com prata sobre formas promastigotas de Leishmania amazonensis e Leishmania braziliensis - Pires, Emanuene Galdino (2015)
Leishmaniasis is a parasitic infectious disease caused by several species of protozoa of the genus Leishmania affecting humans and different animal species, inducing mucocutaneous lesions. The purpose of this study was to evaluate the inhibitory effect of silver doped bioactive glass microparticles over promastigote forms of Leishmania amazonensis (L.Amazonensis) and Leishmania braziliensis (L. braziliensis). Microparticles of bioactive glass (BG) and doped with silver (BGAg1 and BGAg2) belonging to the system 58SiO2·(36-x)CaO·6P2O5·xAg2O with x = 0, 1 and 2 mol%, respectively were synthesized via sol–gel method and characterized by Scanning Electron Microscopy (SEM), Thermal Gravimetric Analysis (TGA), XRay Diffraction (XRD) and Fourier Transform Infrared Espectroscopy (FTIR). The cytotoxity of the BG and BGAg in human cells was assessed from the response of A549 lung adenocarcinoma ephitelial cells line. L.Amazonensis and L. braziliensis promastigote cultures were exposed to BG, BGAg1 and BGAg2 for 24h. Then, 0.5 mM resazurin was added to culture and absorbance readings were assessed after 48, 72 and 96 hours of incubation. The percentage of resazurin reduction per group was obtained from a calculator (AbDSerotec®) and viable promastigote forms were counted on Neubauer chamber. SEM images showed micrometric particles with irregular and porous surface. TGA analysis demonstrated, for samples doped with silver, an endotermic peak around 497ºC associated to silver oxide decomposition. The XRD patterns exhibit mainly amorphous characteristics corresponding to BG. FTIR curves revealed main vibrational modes including Si-O-Si asymmetric stretching vibration (1000-1200 cm-1), Si-O-Si symmetric stretching vibration (750800 cm-1), Si-O-Si bending mode (450-480 cm-1) and PO4-3 antisymmetric bending (570-600 cm-1). Reffering to cytotoxicity, BGAg showed non-toxic behavior. BGAg1- 300µg/mL inihibited L. amazonensis and BGAg2 300 µg/mL inihibited L. braziliensis with 97,6 % and 92% of efficacy, respectively. The count on Neubauer chamber confirmed the efficacy of BGAg2 in 150 e 300 µg/mL concentrations revealing absence of viable cells. In conclusion, the BGAg2- 150 and 300 µg/mL inhibited the growth and proliferation of L.amazonensis and L. braziliensis on promastigote form and could be used in other studies, like in vivo investigations that are necessary to verify the BGAg ativity on Leishmania amastigotes forms.